COVID-19 pandemic impact on occupational health and safety in construction projects: evidence from Jakarta - Fatimah, Putri; Sodri, Ahyahudin; Hamzah, Udi Syahnoedi (Intelektual Pustaka Media Utama, 2023)
The construction industry is commonly perceived as high-risk and involves a large workforce. The COVID-19 poses an additional risk in construction projects to occupational health and safety. DKI Jakarta Province is the epicenter of confirmed COVID-19 cases in Indonesia. This research examined the COVID-19 impact on occupational health and safety in construction projects. A quantitative approach was used, an online distribution questionnaire was conducted to construction workers in DKI Jakarta, with 74 workers participating, and the correlation analysis was using the software IBM SPSS. The result shows that the COVID-19 pandemic increases the risk of occupational health and safety and workers’ anxiety. However, it has had an indirect positive impact on workers’ behavior. Increasing workers’ awareness of occupational health, safety, and healthy lifestyles. The findings of this research provide evidence that the COVID-19 pandemic is a driving force for workers’ behavior changes and raises awareness of workplace safety and health concerns regarding construction projects.